Temperature Characteristics of Photosynthetic and Heterotrophic Activities: Seasonal Variations in Temperate Microbial Plankton - Li, W. K. W. (1987)
The seasonal variation in temperature characteristics of photosynthetic and heterotrophic activities in the microbial plankton of Bedford Basin, Nova Scotia, was investigated. Measurements were made of the photosynthetic uptake of [(14)C]bicarbonate and its incorporation into cellular protein as well as the heterotrophic uptake of (3)H-labeled amino acids and their incorporation into cellular protein. Activity-temperature curves were analyzed objectively by nonlinear estimation of parameters from various mathematical models. Over the seasonal cycle, the cardinal temperatures and a parameter formally equivalent to the thermodynamic enthalpy of activation for most of the four processes measured were positively correlated with the water temperature. The temperature sensitivity of metabolic activity (i.e., change in activity per unit change in temperature) was indexed by the tangent to the activity-temperature curves. When this index was expressed in dimensionless form by normalization to the scaling factor of the activity-temperature curves, the resulting relative temperature sensitivity, evaluated at the prevailing temperature, proved to be statistically invariant throughout the year. During the height of the spring bloom, the water temperature (−0.3°C) was not so low as to inhibit metabolic activity of either the phytoplankton or the bacterioplankton. The evidence suggests that heterotrophic utilization of products is not suppressed during the spring phytoplankton bloom.